A Visible‐Light‐Harvesting Covalent Organic Framework Bearing Single Nickel Sites as a Highly Efficient Sulfur–Carbon Cross‐Coupling Dual Catalyst. (6th April 2021) - Chen, Hui; Liu, Wanlu; Laemont, Andreas; Krishnaraj, Chidharth; Feng, Xiao; Rohman, Fadli; Meledina, Maria; Zhang, Qiqi; Van Deun, Rik; Leus, Karen; Van Der Voort, Pascal
Abstract: Covalent Organic Frameworks (COFs) have recently emerged as light‐harvesting devices, as well as elegant heterogeneous catalysts. The combination of these two properties into a dual catalyst has not yet been explored. We report a new photosensitive triazine‐based COF, decorated with single Ni sites to form a dual catalyst. This crystalline and highly porous catalyst shows excellent catalytic performance in the visible‐light‐driven catalytic sulfur–carbon cross‐coupling reaction. Incorporation of single transition metal sites in a photosensitive COF scaffold with two‐component synergistic catalyst in organic transformation is demonstrated for the first time. Abstract : A dual catalyst (Ace‐COF‐Ni), which is composed of a photosensitive covalent organic framework and single nickel sites, is reported. This dual catalyst exhibits excellent visible‐light and organometallic nickel synergistic catalytic performances for the sulfur–carbon cross‐coupling reaction.